In silico pharmacodynamics, toxicity profile and biological activities of the Saharan medicinal plant Limoniastrum feei - Ouahab Ammar (Universidade de São Paulo, 2017)
ABSTRACT In-silico study was performed to find the pharmacodynamics, toxicity profiles and biological activities of three phytochemicals isolated from Limoniastrum feei (Plumbagenaceae). Online pharmacokinetic tools were used to estimate the potential of Quercetin, kaempferol-3-O-β-D-glucopyranoside (astragalin) and quercitin-7-O-β-D-glucopyranoside as specific drugs. Then the prediction of potential targets of these compounds were investigated using PharmMapper. Auto-Dock 4.0 software was used to investigate the different interactions of these compounds with the targets predicted earlier. The permeability of quercetin was found within the range stated by Lipinski ׳s rule of five. Hematopoietic prostaglandin (PG) D synthase (HPGDS), farnesyl diphosphate synthetase (FPPS) and the deoxycytidine kinase (DCK) were potential targets for quercetin, astragalin and quercetin 7, respectively. Quercetin showed antiallergic and anti-inflammatory activity, while astragalin and quercetin 7 were predicted to have anticancer activities. The activity of Astragalin appeared to be mediated by FPPS inhibition. The inhibition of DCK was predicted as the anticancer mechanisms of quercetin 7. The compounds showed interesting interactions and satisfactory binding energies when docked into their targets. These compounds are proposed to have activities against a variety of human aliments such as allergy, tumors, muscular dystrophy, and diabetic cataracts.